Investigating the anatomy of the employment effects of new business formation - Michael Fritsch; Florian Noseleit (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Recent empirical research has found that the effect of new business formation on employment emerges over a period of about ten years and has identified a 'wave' pattern of these effects. In this study, we decompose the overall contribution of new business formation on employment change into direct and indirect effects. The results indicate that indirect effects of new business formation are quantitatively much more important than the direct effects. Furthermore, we find that regional differences of the employment change generated by new business formation can to a large part be explained by respective differences of the indirect effects. Hence, the interaction of the start-ups with their regional environment plays a great role for explaining their impact on regional development.
Keywords: L26; M13; O1; O18; R11; 330; Entrepreneurship; new business formation; regional development; direct and indirect effects; Unternehmensgründung; Beschäftigungseffekt; Regionale Entwicklung; Deutschland